2020
DOI: 10.1155/2020/8832218
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanism of Berberine on the Dexamethasone‐Induced Injury of Human Tendon Cells

Abstract: Objective. To investigate the effects of berberine (Berb) on dexamethasone- (Dex-) induced injury of human tendon cells and its potential mechanism. Methods. CCK-8 assay was used to explore the appropriate concentration of Dex-induced injury of tendon cells and the doses of Berb attenuates Dex cytotoxicity; cell wound healing assay was used to detect the effects P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A single peritendinous injection of bupivacaine increased apoptosis of endotenon cells, increased pro-MMP-9 expression, increased the type III collagen/type I collagen ratio, and transiently reduced the tensile load of the affected Achilles tendon in rats [ 80 ]. Dexamethasone induced oxidative stress in tendon cells, along with reduced cell migration, proliferation, types I and type III collagen expression as well as activation of apoptosis [ 81 ]. In another study, dexamethasone was also reported to reduce proliferation and tenogenic marker expression in tenocytes in vitro [ 82 ].…”
Section: Clinical and Pre-clinical Evidence Of Potential Sources And ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A single peritendinous injection of bupivacaine increased apoptosis of endotenon cells, increased pro-MMP-9 expression, increased the type III collagen/type I collagen ratio, and transiently reduced the tensile load of the affected Achilles tendon in rats [ 80 ]. Dexamethasone induced oxidative stress in tendon cells, along with reduced cell migration, proliferation, types I and type III collagen expression as well as activation of apoptosis [ 81 ]. In another study, dexamethasone was also reported to reduce proliferation and tenogenic marker expression in tenocytes in vitro [ 82 ].…”
Section: Clinical and Pre-clinical Evidence Of Potential Sources And ...mentioning
confidence: 99%
“…Berberine is an antioxidant found in some plants, such as European barberry, goldenseal, goldthread, Oregon grape, phellodendron, and tree turmeric. Treatment with berberine reversed the effects of dexamethasone on tendon cells [ 81 ]. Oral administration of chloroform extract of Azadirachta indica and methanolic extract of Cuminum cyminum was shown to reduce oxidative stress and collagen cross linking in rat tail tendon in streptozotocin-induced diabetic rats [ 109 , 110 ].…”
Section: Anti-oxidative Therapies For the Promotion Of Tendon Repairmentioning
confidence: 99%